Analisis Dampak Industri Semen Menggunakan Metode Life Cycle Assessment (LCA) Pada PT. Semen Z - Andi Muhamad Rizki Nurzamilov; Praditya Sigit Ardisty Sitogasa (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Semen Z is one of the largest cement supplier companies in Indonesia and will continue to increase every year. The development of the cement industry is in line with the continued development of infrastructure projects, both private and Indonesian government. PT. Semen Z has good integration from raw material providers to cement that is ready to be used by every project that requires it. Development of PT. Cement Z will occur in the quantity of raw materials, human resources, and production processes, up to distribution to consumers. The activities carried out are land clearing/stripping, blasting, excavation and loading, as well as transportation and destruction. Raw materials sourced from this mining process include limestone, silica stone and clay. In this study mining was only carried out on limestone and clay was obtained from suppliers. The units used in the inventory data are limestone and clay raw materials (tons), ammonium nitrate chemicals (tons), diesel fuel (liters), electricity (kWh), emissions (tons), B3 waste (tons), non-B3 waste (tons) and products (tons). Every activity process carried out will have an impact on the environment, so the Company's commitment to a green industry or clean industry is required. To determine the environmental impact analysis on cement production activities, the Company conducted an environmental impact analysis using the Life Cycle Assessment (LCA) method. The aim of this research is to identify improvements in environmental performance, especially those that are hotspots in the Company's production process. The research results show that the highest identification of environmental impacts is obtained from activities at the Limestone mine, in accordance with the Pareto rules approach where if the contributors are more than 80% of the food it will affect the results of the impact analysis obtained.